Meeting the climate change challenge: local government climate action in British Columbia, Canada. (8th August 2020) - Dale, Ann; Robinson, John; King, Leslie; Burch, Sarah; Newell, Rob; Shaw, Alison; Jost, Francois
ABSTRACT: Local governments have a key role to play in implementing climate innovations as they have jurisdiction over a significant portion of greenhouse gas emissions. Meeting the Climate Change Challenge (MC 3 ) is the first longitudinal study exploring climate innovation in Canadian municipalities. A tri-university research collaborative, it focuses on British Columbia (BC), whose voluntary efforts to set and meet climate change goals were far more ambitious than those offered by the federal government (and almost any other province in North America at the time). These efforts included introducing a carbon tax and the Climate Action Charter voluntary agreement in 2007. Since then, 187 of the 190 local governments in BC have signed the Charter to take action on climate change. Research in the first phase of MC 3 explored the dynamics of innovative local responses to the coordinated suite of government legislation, complimentary policy instruments, financial incentives and partnerships with quasi-institutional partners. In the second phase, the 11 original case studies were revisited to explore the nature of transformative change in development paths and indicators of change. Methods include sentiment analysis, decomposition analysis of regional/local emissions, and modelling relationships between climate action co-benefits and trade-offs. This paper provides a synthesis of research outcomes and their implications for environmental governance at multiple scales and the potential of policy innovations to accelerate transformation towards carbon neutral economies. Key policy insights Local governments are on the front line of identifying indicators of change in current development paths and policy innovations to effect the necessary changes for transformation to carbon neutral economies. Barriers to transformational change include lack of coordination or concerted action across multiple scales of governance, electoral cycles and large swings in leadership, and lack of policy coherence across governance levels. Drivers of climate innovation include leadership at multiple levels of governance. Understanding the co-benefits (and trade-offs) of climate actions is important for integrated strategies that achieve broader sustainability goals, as well as accelerating more innovations on climate change.